Myths of the underworld journey Plato, Aristophanes, and the "Orphic" gold tablets - Edmonds, Radcliffe G., III, 1970- (Cambridge University Press, 2004)
Plato, Aristophanes, and the creators of the 'Orphic' gold tablets employ the traditional tale of a journey to the realm of the dead to redefine the boundaries of their societies. These narratives reveal their meanings through close analysis of the specific ways in which each makes use of the tradition.